2006
DOI: 10.1002/eqe.640
|View full text |Cite
|
Sign up to set email alerts
|

Energy dissipation in rocking bridge piers under free vibration tests

Abstract: This research aims to investigate the dynamic characteristic of rocking bridge columns subjected to quick release loads. Precast columns anchored by unbonded steel bars at the centre of each column can rock on the foundation surface without inducing any residual deformation after earthquakes. The restoring force of columns relies on gravity load from the superstructure and tensile strength in anchor bars. Radiation damping is evaluated through each impact of column rocking. To validate the theoretical damping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…Therefore, with significant rocking motion, the tested damping of bridges can be reasonably predicted by the analytical model. The rocking behavior of a single column without a superstructure under free vibration has been previously investigated by Cheng [14]. Test results showed that radiation damping was small; that is, within 5% and agreed well with the analytical model.…”
Section: Damping Evaluationssupporting
confidence: 64%
See 1 more Smart Citation
“…Therefore, with significant rocking motion, the tested damping of bridges can be reasonably predicted by the analytical model. The rocking behavior of a single column without a superstructure under free vibration has been previously investigated by Cheng [14]. Test results showed that radiation damping was small; that is, within 5% and agreed well with the analytical model.…”
Section: Damping Evaluationssupporting
confidence: 64%
“…This damping behavior can be also found in the context of wave propagation through the soil under the structural foundation. Cheng [14] studied the impact behavior of free or anchored columns through quick release tests. It was found that damping prediction for rocking columns with slenderness (height vs. width) 4 or 6 agreed well with the test results.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng tested four geometrically different controlled rocking concrete columns under free vibration. The four columns had dimensions of: (a) 30 × 30 × 60, (b) 30 × 30 × 120, (c) 30 × 30 × 180, and (d) 60 × 60 × 240 cm 3 (thickness × width × height) and were anchored to their foundations using unbonded steel bars.…”
Section: Impact Energy Lossmentioning
confidence: 99%
“…Considering a recent work on characterization of free‐standing rocking bodies, this paper addresses impact energy loss in controlled rocking structural members using the coefficient of restitution ( r ) per Kalliontzis et al, which introduces an instantaneous reduction in the kinetic energy of the members at impacts. First, the accuracy of this approach is investigated using (a) recent experiments of three controlled rocking members of various geometries and levels of initial posttensioning force and (b) experimental data from controlled rocking members tested by previous researchers . Second, using the r approach, a controlled rocking model (CRM) is developed to capture the experimental responses of controlled rocking members and investigate their lateral displacement responses under horizontal base excitations.…”
Section: Introductionmentioning
confidence: 99%
“…An and Kiyomiya [19] and Chen et al [20], in two independent studies, explored analytically and experimentally the feasibility of utilizing a rocking mechanism for earthquake protection of slender viaduct piers, showing in both cases a significant positive effect in mitigating the seismic response. Finally, Cheng [21] reported the results of free vibration tests carried out on stepping precast bridge columns, in which energy is dissipated through impacts and slips on the foundation plate.…”
Section: Introductionmentioning
confidence: 99%